The Effect of the Tarbiyah Islāmiyah Implementation on Akhlakul Karimah of Students at College of Islamic Sciences and Arabic Language (STIBA) of Makassar - M. Kasim; Bahaking Rama; A. Marjuni; Misykat Malik Ibrahim (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This research aims to discuss the influence of the implementation of Tarbiyah Islāmiyah on morality at the Makassar College of Islamic and Arabic Sciences (STIBA). The main issue discussed is how much influence the implementation of Tarbiyah Islāmiyah has on students at the Makassar College of Islamic and Arabic Sciences (STIBA), with sub-problems, namely: 1) How to describe the implementation of tarbiyah rūhiyah at STIBA Makassar; 2) How to describe the implementation of tarbiyah ṡaqafiyah in STIBA Makassar; 3) How to describe the implementation of tarbiyah jasadiyah in STIBA Makassar; 4) How is the description of the morality of STIBA Makassar students; and 5) How much influence the implementation of tarbiyah rūhiyah on students' morality at STIBA in Makassar; (6) the effect of the implementation of tarbiyah ṡaqāfiyah on morality karimah, Based on the results of the study obtained regression equation Ŷ = 117,506 + 0.552X_1 and the value of F_hitung greater than the value of F_tabel (11,575>2.70), with a sig value smaller than 0.05 (0.005<0.05), this indicates that the implementation of tarbiyah ṡaqāfiyah has an influence on akhlakul karimah with a determination rate of 11.1%; (7) the effect of the implementation of tarbiyah jasadiyah on moral karimah, based on the results of research obtained regression equations Ŷ = 84,742 + 0.711X_1, and the value of F_hitung greater than the value of F_tabel (20,551>2.70), with a sig value smaller than 0.05 (0.005<0.05), this shows that the implementation of tarbiyah jasadiyah has an influence on karimah morality with a determination rate of 18.1%; and (8) the influence of the implementation of tarbiyah rūhiyah, tarbiyah ṡaqāfiyah, and tarbiyah jasadiyah together against morality karimah, based on the results of research obtained regression equation Ŷ = 49,626 +0.303X_1 +0.388X_2 +0.280X_3, and the value of F_hitung> F_tabel (9,807>2.47) with a sig value smaller than 0.05 (0.005<0.05), this shows that the implementation of tarbiyah rūhiyah, tarbiyah ṡaqāfiyah, and tarbiyah jasadiyah together has an influence on morality with the level of determination 21.9%. Implications of this study on student morality, that 1) the construction of morality of students in universities can be done through the Islāmiyah tarbiyah program as an extracurricular activity; 2) The application of student moral development can be done through the integration of the process of strengthening; 3) In intervening in the implementation of the Islāmiyah tarbiyah program at universities can be applied by making rules and signs of morality both on campus and off campus.